Implementasi Togaf Untuk Perancangan Arsitektur Rumah Sakit - Zainal Nur Ali; Geubrina Raseuki; Nia Ramadani; Hafizh Fahriza; Nadila Rizkika Dwi Ananada Matondang; Raissha Vathyma Azzahra; Putri Syahbillah Hidayat; Ika Yusnita Sari (CV. ITTC INDONESIA, 2026)
This research analyzes the issue of digital transformation in hospitals in North Sumatra, characterized by information system fragmentation, application duplication, and inconsistent integration of clinical and administrative data, which impacts operational efficiency and service speed. This research develops an enterprise architecture using the TOGAF (The Open Group Architecture Framework) approach thru the TOGAF ADM (Architecture Development Method) architecture development method to achieve alignment between business, data, application, and information technology (IT) architectures. This research method was conducted descriptively, with primary data collected thru interviews and observations of the service process, as well as secondary data obtained from Indonesian hospital datasets and relevant supporting documents. The research objects consist of 10 hospitals with B, C, and D classes. The design process was carried out thru seven ADM phases, aiming to produce an architectural blueprint and implementation recommendations. The evaluation was conducted thru gap analysis and descriptive statistics to assess the level of system integration before and after the implementation of TOGAF ADM. Data shows that the average integration increased from 65% to 77.2%, representing a 12.2-point increase, with variations ranging from 5 to 15 points. In B-class hospitals, the average integration increased from 80% to 92.3%. For C-class hospitals, the increase was from 62% to 76%, while D-class hospitals showed an increase from 50% to 57.5%. The highest recorded increase was 15 points in some hospitals, while the lowest increase found was 5 points in D-class hospitals. Hospitals with larger capacities showed an improvement in operational efficiency between 20% and 25%, which was related to improvements in electronic medical record (EMR) integration and hospital management systems. The main recommendations of the research include phased and modular implementation thru cloud storage, strengthening data governance, and Application Programming Interface-based integration to reduce costs and improve interoperability.